Answer: none
Step-by-step explanation:
(A)
(16÷32/10) ×2 + 0.2×(90)
Using bodmas principle ; solve bracket
(16×10/32)×2 + (2/10×90)
10+18 =28
(B)
{(16÷32/10) × (2+2/10)} ×90
Open brackets
{(16×10/32) × (22/10)} ×90
(5×11/5) ×90
11×90 = 990
(C)
16÷{(32/10×2) + (2/10×8)} +82
Open brackets, solve division first, dolled by addition
16÷(32/5 + 8/5) +82
16÷(40/5) +82
16÷8 +82
2+82= 84
(D)
[16÷(32/10 ×2) + 0.2× (90)]
16÷ (32/5) + 2/10 ×90
Solve division
16×5/32 + 18
5/2 + 18
L.c.m of denominator (2&1) =2
(5+36) / 2 = 41/2
=20.5
<span>f(x) = -6x +6
to find inverse
x = -6y + 6
6y = 6 - x
y = 1 - x/6
Answer
</span>f^–1(x)= 1 - x/6
Answer: b
Explanation: cube root is equal to the power of 1/3
Multiply the exponents 24/3=8
Answer: B. Similar - AA
Step-by-step explanation:
The AA or Angle-Angle postulate states that if two corresponding angles are congruent, then the triangles are congruent.
Answer:the anwser is B
Step-by-step explanation:
Thw symbol in the equation means least or equal to 5.